PARODY AND INTELLECTUAL PROPERTY LAW (IN THE CONTEXT OF EMERGING FASHION LAW) - Silhankova, Sarka (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
This article deals with the relationship between parody and intellectual property law. First, the author presents the concept of parody in European law. In this context, the CJEU judgment delivered in the case Deckmyn v. Vandersteen is extensively analyzed. In addition to discussing parody within the framework of copyright and trademark law, the author presents several cases from the emerging area of fashion law. As the CJEU has not ruled on any case concerning fashion law, the author mainly focuses on the United States case law. Most cases related to fashion law usually end in confidential agreements and out of court settlement. Yet, several cases were decided in national court proceedings. All these cases illustrate how parody is used ineverydaylife in the fashion world.